ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII MTS Al-MUBAROKAH PADA MATERI STATISTIKA - Radifan Irsaly; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to analyze mathematical problem solving skills in statistical material. This research was conducted using qualitative methods. The subjects of this study were students of class VIII MTS Al-Mubarokah with a sample of 30 people. Data collection techniques using student test results based on indicators of mathematical problem solving ability; 1) identify the adequacy of the problem; 2) planning problem solving; 3) selecting and implementing problem solving strategies; 4) verify the results of problem solving. Based on the results and discussion of the research, it shows that the difficulty of students in working on story-shaped questions occurs in the indicator of identifying the adequacy of the problem with an error percentage of 90% and occurs in the indicator of choosing and implementing problem solving strategies with an error percentage of 85% and the following data are included in the high category. The causative factors include; students do not understand the basic concepts of statistics, are not able to identify problems correctly and precisely, are not able to communicate problems with mathematical models.